Strengthening the Spirituality of the Congregation Through Mosque-Based Jalalain Interpretation Studies: A Participatory-Reflective Approach: Penguatan Spiritualitas Jamaah Melalui Kajian Tafsir Jalalain Berbasis Masjid: Pendekatan Partisipatif-Reflektif - Muhammad Syarofi; Fadlillah (Journal of Research and Community Service, 2025)
Spiritual development of mosque congregations plays a strategic role in strengthening faith quality and moral integrity amidst the complexities of modern life. However, religious studies conducted in mosques generally remain normative and tend to overlook critical reflection on latent faith-related issues, such as hypocrisy and spiritual integrity degradation. This community engagement programme aims to implement a reflective-participatory Qur’anic exegesis approach through the study of Tafsir Jalalain on QS. Al-Baqarah verse 17 as a model for strengthening the spiritual development of the congregation at Al-Ihsan Mosque, Jember Regency. The programme employed a Participatory Action Research (PAR) design, involving 30–40 active congregants as participants. Data were collected through participatory observation, in-depth interviews, written reflection sheets, and systematic field notes, and were analysed using source and method triangulation techniques. The findings indicate significant improvements in self-awareness, moral reflection, commitment to behavioural change, and reinforcement of religious practices among congregants. The reflective exegesis-based learning model proved more effective in fostering deep spiritual transformation and positive social behaviour than conventional sermon-based approaches. This programme contributes to the advancement of classical Qur’anic exegesis as a reflective instrument in mosque-based community engagement, offering an applicable, participatory, and sustainable model for spiritual development.